2014
DOI: 10.1007/s00038-014-0602-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension: diagnosis, control status and its predictors in general population aged between 15 and 75 years: a community-based study in southeastern Iran

Abstract: Hypertension affected almost one-fifth of the population. Given the poor control in diagnosed hypertensive patients, it is alarming that the current health system in urban areas in Iran is not effective enough to control the epidemic spread of non-communicable diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…This prevalence was similar to other studies that investigated both sexes, (4,12) but lower than the levels found in studies undertaken in Rio Grande do Sul (75%) (13) and São Paulo (78%). (14) It should be highlighted that the variation in the method used to verify pressure levels influences the achievement of better blood pressure levels and that hypertension control results from a complex system of biological, socioeconomic, cultural and health structure aspects.…”
Section: Discussionsupporting
confidence: 89%
“…This prevalence was similar to other studies that investigated both sexes, (4,12) but lower than the levels found in studies undertaken in Rio Grande do Sul (75%) (13) and São Paulo (78%). (14) It should be highlighted that the variation in the method used to verify pressure levels influences the achievement of better blood pressure levels and that hypertension control results from a complex system of biological, socioeconomic, cultural and health structure aspects.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have found similar results to those of our study. [141618] HTN is a highly prevalent disorder in the elderly. Due to structural alterations of arterial wall occurring with aging, arterial stiffness increases and in turn SBP increases in old people.…”
Section: Discussionmentioning
confidence: 99%
“…[24] In different countries this awareness has been reported from 25 to 75%. [25] Awareness in Yazd is lower compared to most studies in Iran (69.2% in Isfahan , [9] 60.5% in Tabriz, [12] and 57% in Kerman [26] . It is slightly higher than Golestan's (46.2%) and a previous study in Yazd (43.7%).…”
Section: Discussionmentioning
confidence: 61%